Fear of Missing Out and its impact: exploring relationships with social media use, psychological well-being, and academic performance among university students - Abd Ellatif Elsayed, Hala (Frontiers in Psychology, 2025)
BackgroundThe increasing prevalence of social media has given rise to the Fear of Missing Out (FoMO) phenomenon, characterized by an acute awareness of the rewarding experiences others might be enjoying. FoMO is hypothesized to affect various aspects of individuals’ lives, including their psychological well-being and academic performance. This study explores these relationships among university students, a demographic particularly vulnerable to social media influences.ObjectiveTo examine the relationships between FoMO, social media use, psychological well-being (as measured by life satisfaction), and academic performance (as measured by GPA) among university students and determine the mediating roles of FoMO and social media use.MethodsA quantitative, correlational design was employed, collecting data from 521 university students through a cross-sectional survey. Participants completed the Fear of Missing Out Scale (FoMO), the Satisfaction with Life Scale (SWLS), and self-reported GPA. Social media use was assessed via a customized questionnaire. Data were analyzed using SPSS, employing correlation analysis, multiple regression, and mediation analysis.ResultsFindings indicated a strong positive association between FoMO and social media use (R2 = 0.633, p < 0.001), suggesting that higher levels of FoMO lead to increased social media engagement (B = 0.834, p < 0.001). Contrary to expectations, FoMO was positively rather than negatively correlated with life satisfaction (R2 = 0.064, p < 0.001, B = 0.158). Additionally, a strong positive correlation was observed between social media use and academic performance (Spearman’s rho = 0.765, p < 0.001). Mediation analyses revealed that FoMO does not significantly mediate the relationship between social media use and life satisfaction, as the indirect effect was not statistically significant (B = 0.0785, 95% CI: −0.0164 to 0.1467). Similarly, the non-significant indirect effect indicated that social media use did not mediate the relationship between FoMO and academic performance (B = 0.005, 95% CI: −0.0045 to 0.0146). Moderation analyses showed that FoMO moderates the relationship between social media use and life satisfaction, where social media use hurt life satisfaction at low levels of FoMO (B = −0.1713, p = 0.0001) but had a positive effect at high levels of FoMO (B = 0.2848, p < 0.0001). This suggests that individuals with high FoMO may derive psychological benefits from social media use. Additionally, results indicated that social media use moderates the relationship between FoMO and academic performance, where FoMO had a significant adverse effect on GPA at low social media use (B = −0.030, p < 0.0001). Still, this effect became non-significant at high levels of social media use (B = 0.0097, p = 0.1028). Finally, life satisfaction moderates the relationship between FoMO and social media use, with higher life satisfaction strengthening the positive association between FoMO and social media use (B = 0.9277, p < 0.0001).ConclusionThese findings highlight the complex interplay between FoMO, social media use, life satisfaction, and academic performance. While FoMO increases social media engagement, its positive association with life satisfaction contradicts theoretical expectations. These results underscore the importance of considering psychological and social factors when evaluating the impact of social media use among university students.